Ridley Road [videorecording (DVD)] - O'Casey, Agnes; Kinnear, Rory, 1978-; Marsan, Eddie (PBS, 2022)
It tells the story of Vivien Epstein, a young Jewish woman who after falling in love with a member of the '62 Group', rejects her comfortable middle-class life in Manchester and joins the fight against fascism in London. Inspired by true events, it follows Vivien as she goes undercover into the NSM, a neo-Nazi movement that is becoming increasingly prominent in London.